Banking systems (Thomson South-Western, 2005)
Explore the principles and practices of banking and credit in the United States with Banking Systems. This exciting, new text guides users through an overview of financial services, including information on human resources, marketing, and ethics. Each chapter is divided into several lessons, making the content easy for users to understand and retain. Extensive activities within the text bring realism to the course and let users learn by doing.